ANALISIS MANAJEMEN PERSEDIAAN BAHAN PADA UKM MAKANAN KALENG - Sumantika, Arsyad; Sirait, Ganda (Universitas Putera Batam, 2024)
Material inventory is a fundamental aspect of the company. The smoothness of the production process is not only based on the level of effectiveness in the production process, but also on other processes related to material inventory. If materials are in short supply, the production process will experience disruption which results in financial and non-financial losses. If there is too much material inventory, then the material storage costs borne by the company will be greater. The aim of this research is to maximize material supplies and determine the right time to reorder raw materials. The methods used are EOQ, ROP, and ITO. Data collection was carried out quantitatively at a fish canned food company. Based on the calculation results, it was found that the economic level of purchasing main raw materials using the EOQ method approach was 25 kg per order and the recommended reorder amount was 10 kg per order, while for safety sticks the recommended amount was 4.4 kg/day.